The development trend，focus and path of digital village - Song Shuyuan; Fan Guohao; Wang Yan; Xia Lei; Zhang Min (Dianzi Jishu Yingyong, 2022)
The construction of digital village is a strategic direction for rural revitalization, and more importantly, an important support for the landing of digital China. The development of China′s village has characteristic political, economic and cultural forms, and also carries a unique development mission in the national strategy. Around the urgent demand of expanding domestic demand, accelerating factor flow and smoothing the large domestic circulation, it is urgent to promote the upgrading of digital village construction. The digital city has formed a good foundation and advantages in the development environment, core technology, market space and supervision guarantee, which becomes the core leading and important guarantee for the development of digital village.